Cardiac Dysfunction Associated with Lacosamide in a Premature Infant with Hypoxic Ischemic Encephalopathy: A Case Report - Trassanee Chatmethakul; Amy H. Stanford; Danielle R. Rios; Adrianne R. Bischoff; Theresa Czech; Patrick J. McNamara (American Journal of Perinatology Reports)
Lacosamide (Vimpat Harris FRC Corporation, 2022 UCB, Inc. Smyrna, GA 30080) is an antiseizure medication, which acts through blockage of voltage-gated neuronal sodium channels. Its recent implementation in the neonatal population has been extrapolated from adult and pediatric data suggesting a favorable safety profile. Of note, preterm infants have unique developmental characteristics that may predispose them to increased risk of adverse reactions. We present a case of a preterm neonate who developed left ventricular dysfunction coinciding with the initiation of lacosamide.